2021
DOI: 10.2807/1560-7917.es.2021.26.24.2100439
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of clade 2.3.4.4b A(H5N8), a highly pathogenic avian influenza virus, from a worker during an outbreak on a poultry farm, Russia, December 2020

Abstract: This study presents the isolation of influenza A(H5N8) virus clade 2.3.4.4b from a poultry worker during an outbreak of highly pathogenic avian influenza A(H5N8) among chickens at a poultry farm in Astrakhan, Russia in December 2020. Nasopharyngeal swabs collected from seven poultry workers were positive for influenza A(H5N8), as confirmed by RT-PCR and sequencing. The influenza A(H5N8) virus was isolated from one of the human specimens and characterised. Sporadic human influenza A(H5)2.3.4.4. infections repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 11 publications
3
71
0
Order By: Relevance
“…To the editor: We concur with the Wen et al that currently, the S28N amino acid substitution in the neuraminidase (NA) of influenza A(H5N8) viruses is rare [1]. This conclusion was based on the observation of the authors that the amino acid substitution is only found in 0.39% of the influenza A(H5N8) strains deposited in GISAID by 28 August 2021, which is also mentioned in our paper [2].…”
supporting
confidence: 88%
See 1 more Smart Citation
“…To the editor: We concur with the Wen et al that currently, the S28N amino acid substitution in the neuraminidase (NA) of influenza A(H5N8) viruses is rare [1]. This conclusion was based on the observation of the authors that the amino acid substitution is only found in 0.39% of the influenza A(H5N8) strains deposited in GISAID by 28 August 2021, which is also mentioned in our paper [2].…”
supporting
confidence: 88%
“…Rare detection of the S28N mutation in cell isolates (one in 72) does not support the hypothesis of strong selection for the S28N mutation in MDCK cells. However, cultivation of A/Astrakhan/3212/2020 and the presence of 28N in H5N6, H5N1 and H7N9 viruses that infect humans [ 2 ] suggest a possibility that the S28N mutation may provide a certain advantage in the selection of the virus variant in mammalian cells. This hypothesis needs to be studied further.…”
mentioning
confidence: 99%
“…In February 2021, the Russian Federation reported detecting 7 cases of asymptomatic human infection with HPAI H5N8 clade 2.3.4.4b viruses in poultry farm workers, linked to a poultry outbreak ( 9 ). However, a serologic study revealed the presence of antibodies to an HPAI H5N8 clade 2.3.4.4 virus in 61 of 760 serum samples from persons who had had contact with infected or deceased birds during the 2016–17 HPAI outbreaks in Russia ( 10 ), providing evidence of overlooked human infection.…”
mentioning
confidence: 99%
“…Through investigations using Madin-Darby Canine Kidney (MDCK) cells in a focus reduction neutralization assay (FRNA), four of the seven poultry workers who were PCRpositive had FRNA titers in their first serum samples [17]. Seroconversion was detected in their second serum samples 14 days later, with one having a four-fold increase and two having a two-fold increase in FRNA titer compared to their first serum sample.…”
Section: Epidemiology Of H5n8mentioning
confidence: 99%